Retrofitting old shop houses using Building Information Modelling (BIM) for improving building construction / Endok siti nurul shafiqah ... [et al.] - Hamzah, Endok siti nurul shafiqah; Horace Mui K. W, K. W, Horace; Akasah, Zainal Abidin; Nik Soh, Nik Mohd Zaini (2019)
Building Information Modelling (BIM) is a set of digital tools that can manage construction projects effectiveness. BIM has been used by the Architecture, Engineering and Construction (AEC) industries in Malaysia. The application of BIM to retrofit existing buildings faces challenges which could be due to the multi-disciplinary nature of information exchange, the timeliness of the exchange, including the wide array of technological components which are needed to ensure an optimal exchange. So, the need to refurbish the old shop is becoming more important than the construction of new buildings. Modern technologies allow professionals to do this to turn the building structures capable to meet the users' comfort with a considerable energy saving. The aim of this paper is to identify BIM implementation of old shop building using new BIM and to model 3D simulation using BIM software. From the literature review previous BIM studies on definition and history of BIM, construction issues, application BIM tools in construction project as well as benefit of BIM. The results of the analysis were establish from surveys of questionnaire and 3D simulation. BIM helps to increase construction project efficiency and effectiveness and implementing BIM in construction projects can lead to successful construction of projects and can increase the overall quality of projects and can improve image of the construction industry.